Thermochronology and exhumation history of the basement and sediments of the NNE border of the Paraná basin, Brazil - Resende, Rosana Silveira [UNESP]; Tello Sáenz, Carlos Alberto [UNESP]; Dantas, Elton Luiz; Hackspacher, Peter Christian [UNESP]; Chavez Machaca, César Anthony; Glasmacher, Ulrich A. (Elsevier, 2020)
Combined zircon fission-track (FT) and U–Pb dating were used to obtain correlated cooling ages and tectonic processes in the eastern border of the Phanerozoic Paraná Basin, a large cratonic sedimentary basin in South America deposited over Precambrian basement, which is represented mainly by the Neoproterozoic Brasília Orogenic Belt. Zircon ages obtained for clastic sediments suggest that the provenance history of the Paraná Basin was derived chiefly from the proximal basement sources. Twelve zircon samples were collected, from which 194 grains were analyzed and simultaneously dated by the FT and U–Pb methods, and 146 zircon grains were additionally dated only through the fission-track method (FT). The standard sample of Fish Canyon Tuff (FCT) was also analyzed through FT and U–Pb, and the age results of 26.6 ± 1.1 Ma, and 28.33 ± 0.68 Ma, respectively, are consistent with the literature data. The fission-track ages, obtained for the Araxá (~330 Ma) and Canastra (~500 Ma) Groups, and Piumhi Massif (~700 Ma) pertaining to the Brasília Belt, in average increase towards the São Francisco Craton. This fission-track age pattern can be linked to the temperature and exhumation of each one of these units. The U–Pb detrital zircon ages obtained for the basement units range from 1.6 to 3.2 Ga and indicate different provenance sources in the evolution of the Brasília Belt. However, it is clear that the main sources of metasedimentary rocks are derived from the São Francisco-Congo Craton. For samples collected in the NNE border of the Paraná Basin, FT ages were obtained for 127 zircon grains with ages ranging between 100 and 600 Ma. Forty of these grains dated simultaneously with FT and U–Pb bear mean age populations of 0.6 and 1.0 Ga, and subordinately between 1.5 and 2.5 Ga. These results suggest that the units that represent the São Francisco Craton's Neoproterozoic passive margin were being formed with depositional sediments 1.0 Ga ago and their recycling was the main source for the zircon derivation recorded in the Paraná Basin sediments. An important methodological result of this work is that U–Pb radiometric dating was done in the same areas of single zircon crystals employed to determine the FT ages, which improved the concordance in the U–Pb ages. As such, U–Pb dating on zircon micro areas that have undergone leaching, metamictization or another type of lattice damage was avoided.
Keywords: Brasília belt; Fission-track method.; LA-MC-ICP-MS; Paraná basin; U–Pb in situ dating; Zircon